Strategic Planning for Communities, Non-profit Organizations and Public Agencies - Henry Cothran; Rodney Clouser (EDIS)
FE648, a 7-page fact sheet by Henry Cothran and Rodney Clouser, introduces the concept of strategic planning, describing what it is and why organizations should engage in strategic planning. It explains the process, defining six broad tasks that must be accomplished. Includes references. Published by the UF Department of Food and Resource Economics, July 2006.